Relationships between Athletic Motor Skill Competencies and Maturity, Sex, Physical Performance, and Psychological Constructs in Boys and Girls - Ben J. Pullen; Jon L. Oliver; Rhodri S. Lloyd; Camilla J. Knight (MDPI AG, 2022)
The purpose of this study was to examine the relationships between athletic motor skill competencies (AMSC), maturation, sex, body mass index, physical performance, and psychological constructs (motivation to exercise, physical self-efficacy, and global self-esteem). Two-hundred and twenty-four children aged 11-13 years old were included in the study and sub-divided by sex. The athlete introductory movement screen (AIMS) and tuck jump assessment (TJA) were used to assess AMSC, while standing long jump distance assessed physical performance. Online surveys examined participants' motivation to exercise, physical self-efficacy, and self-esteem. Trivial to moderate strength relationships were evident between AMSC and BMI (boys: rs = −0.183; girls: rs = −0.176), physical performance (boys: rs = 0.425; girls: rs = 0.397), and psychological constructs (boys: rs = 0.130-0.336; girls rs = 0.030-0.260), with the strength of relationships different between the sexes. Higher levels of AMSC were related to significantly higher levels of physical performance (d = 0.25), motivation to exercise (d = 0.17), and physical self-efficacy (d = 0.15-0.19) in both boys and girls. Enhancing AMSC may have mediating effects on levels of physical performance and psychological constructs in school-aged children, which may hold important implications for physical activity levels and the development of physical literacy.